HUBUNGAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU PAUD DI KECAMATAN RIMBO TENGAH KABUPATEN BUNGO JAMBI - Ulya, Ilmiyati; Zulminiati, Zulminiati (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2019)
Abstract: This study was to look at the relationship of school principals leadership to the performence of PAUD teachers in Rimbo Tengah subdistrict, Bungo Jambi district. The type of research was correlation using a quantitative method that involved qestionnaire data collection. Data processing using SPSS version 16. From the data obtained the coefficient of determination of the leadership of the principal is 0,719. The coeffecient of headmaster’s leadership on teacher performance in PAUD is 0,517. This means that leadership at 51.7% of the performance of PAUD teachers is significant at the 5%. So the principal’s leadership to the performance of PAUD teachers in Rimbo Tengah subdistrict Bungo Jambi district by 51,7% correlation between.